Analyzing Proximate Composition of Macro Nutrients of Sri Lankan Cassava Variety "Kirikawadi" - Somendrika, M.A.D.; Wickramasinghe, I.; Wansapala, M.A.J.; Peiris, S. (Pakistan Journal of Nutrition, 2016)
Cassava (Manihot esculenta) which is considered as the third most important food source in tropics is a cheap and reliable food source for people in developing countries. This study was sought to analyze the proximate (moisture, ash, total fat, crude fibre, protein and carbohydrate) in the peel and the flesh of "Kirikawadi" variety. The proximate composition (moisture, ash, crude fibre, protein and total fat) of the six samples was determined using standard methods with three replicates. The carbohydrate content was calculated by the difference. The peel contain significantly high amount of moisture (72.63±0.67%), fat (0.68±0.08%), protein (1.73±0.09%) and fibre (2.31±0.02%) than the flesh, where the flesh contain significantly (p<0.05) high amount of ash (1.32±0.03%) and carbohydrate (33.73±1.69%). A negative correlation was significantly exist in between the moisture content of the flesh, the fat content and carbohydrate content of flesh. The protein content in the flesh was correlated negatively and significantly with the protein content of the peel. There was a significant positive correlation exist in between carbohydrate content and the fat content in the flesh.